2013
DOI: 10.5267/j.dsl.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

An exploration study on influential factors on information and communication technology

Abstract: During the past few years, information and communication technology (ICT) has revolutionized banking industry in the world. People are now able to do their business banking activities such as bill payments, transfer funds, etc. through the art of ICT features such as automatic teller machines, internet or telephone banking services. This paper performs an empirical investigation to find important factors influencing ICT implementation in Iranian banking industry. The survey uses factor analysis to find importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Li et al (2011) presented a Web-based hybrid knowledge automation system, called WebDigital for analyzing digital marketing strategies and reported that the Web-enabled knowledge automation system could be an efficient and effective method for improving the digital marketing strategy formulation process and its output. Azad et al (2014a) performed an empirical investigation to detect important factors influencing information and communication technology (ICT) implementation in Iranian banking industry. The survey applied factor analysis to find important factors and reported six factors influencing ICT including efficiency approach, new advanced technological achievements, human resource management, service strategy, growth strategy and supporting systems.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2011) presented a Web-based hybrid knowledge automation system, called WebDigital for analyzing digital marketing strategies and reported that the Web-enabled knowledge automation system could be an efficient and effective method for improving the digital marketing strategy formulation process and its output. Azad et al (2014a) performed an empirical investigation to detect important factors influencing information and communication technology (ICT) implementation in Iranian banking industry. The survey applied factor analysis to find important factors and reported six factors influencing ICT including efficiency approach, new advanced technological achievements, human resource management, service strategy, growth strategy and supporting systems.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2006) investigated different issues such as how technology capability influences business performance, whether the linkage between technology capability and business performance depends on specific contexts and why some high-tech firms of strong technological capability fail to reach their objectives. Azad et al (2014) performed an empirical investigation to detect important factors influencing information and communication technology (ICT) implementation in Iranian banking industry. The survey applied factor analysis to find important factors using a questionnaire consist of 26 variables and detected six factors influencing ICT including efficiency approach, new advanced technological achievements, human resource management, service strategy, growth strategy and supporting systems.…”
Section: Introductionmentioning
confidence: 99%